Development of a rapid and reliable analytical method for screening poloxamer 188 for use in cell culture process. (12th March 2019) - Bareford, Lisa; Peng, Haofan; Ali, Amr; Kolwyck, David; Dickens, Jason
Abstract: Poloxamer P188 is a common nonionic surfactant additive used in cell culture media as a cellular protectant from the hydrodynamic forces and shear stress during bioprocessing. Presence of a hydrophobic high molecular weight impurity contaminant has been shown to compromise its protective properties and lead to batch failure. In this work we present, a reliable, sensitive, and rapid analytical method to detect and quantify the contaminant impurity in poloxamer 188. This method replaces a laborious and time‐consuming functional test in the form of a shake flask assay. The method is based upon reversed‐phase liquid chromatography with charged aerosol detection, simple mobile phase compositions, and a three‐step gradient. The method was optimized to resolve the impurity from the main P188 fraction in less than 10 min. Analytical method qualification and functional test comparison demonstrate equivalent or better high throughput impurity screening performance. Attempts to identify the impurity and establish suitable method positive control standards are also discussed.